Implementation of Corporate Social Responsibility In Indonesia Based on Ius Positum And Islamic Principles - Supardi Supardi (Journal of Governance, 2022)
Corporate Social Responsibility (CSR) is a form of a company's responsibility to the community and the surrounding environment that are affected by the company's activities. CSR is a familiar term when viewed from a legal perspective, including in Islamic law. So far, there has been no alternative concept of CSR that has been extracted from the values contained in the culture and belief system, including Islamic teachings, even though the values built by each culture and belief aim to achieve community welfare. Based on this, this study aims to find out whether the existing Corporate Social Responsibility (CSR) concept follows the principles of Islamic law. Has Islam regulated this? So that the activities carried out by the company are of worship value for business actors. This is normative legal research that refers to primary, secondary and tertiary materials. The result of the study is that CSR is contained in the teachings of Islam; Islam has long been building a system of life-based on social principles and justice. Islam strongly supports CSR because it cannot be denied that business creates many unexpected social problems. As a result, it is the responsibility of the company and the company to fix the problem. This is natural because they need to explore various natural resources for business sustainability. Therefore, they must be responsible for the community and the environment in return.